Pengembangan Kartu Fisika Stop-Go (Fikaso) Pada Materi Gelombang Cahaya untuk Meningkatkan Hasil Belajar Peserta Didik - Alvian Ariantoro; Mita Anggaryani (UNIB Press, 2023)
Education is an integral part of a nation’s life. The Indonesian Government has taken crucial action to improve the quality of education, starting with improving the curriculum, teachers' quality, and the use of technology in class. Curriculum 2013 encourages students to be more active in their learning process. However, teachers sometimes only rely on textbooks so that learning objectives are not achieved and students are less motivated to learn the topic. This research aims to develop media that can facilitate cooperation between teachers and students, namely the Fikaso card game. More specifically, this research was conducted to describe the validity, effectiveness, and practicality of Fikaso cards in learning to improve students' learning outcomes. The study was developed with the Analysis, Design, Development, Implementation, and Evaluation (ADDIE) model. The results of the discussion show that the Fikaso cards that have been developed are declared: (1) Very valid or very feasible to use with an average percentage of 89%, (2) Effective with an effectiveness percentage of 73%, and can improve student learning outcomes with an N-gain value of 0.56 which is categorized as a moderate increase, and (3) Very practical to use with an average percentage of 92%.